Effect of Salicylic Acid and 5-Sulfosalicylic Acid on UV-Vis Spectroscopic Characteristics, Morphology, and Contact Angles of Spin Coated Polyaniline and Poly(4-aminodiphenylaniline) Thin Films. (31st March 2015) - Sironi, A.; Marinotto, D.; Riccardi, C.; Zanini, S.; Guerrini, E.; Della Pina, C.; Falletta, E.
Abstract : Polyaniline and poly(4-aminodiphenyl)aniline have been prepared following two different synthetic protocols (a traditional method and a "green" method). Both the polymers have been spin coated with salicylic acid and 5-sulfosalicylic acid as the dopants, in order to obtain them in form of thin films. These materials have been characterized, thereof achieving important information on their water contact angles and surface morphology.